MENINGKATKAN KEMAMPUAN MEMAHAMI ISI TEKS FABEL PADA SISWA KELAS VII SMPN 5 SAMALANTAN - Mitha, Mitha; Syam, Christanto; Syambasril, Syambasril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is motivated by the low interest in reading and student motivation in learning to read comprehension of grade VII SMPN 5 Samalantan district of Bengkayang regency. The problem of this research is on planning, implementation and outcomes to improve the ability to understand the text fable using Directed Reading Activity method. This study is expected to provide benefits to researchers, teachers, students and schools. The method used in this research is descriptive qualitative method to form a Class Action Research.Sources of data in this study were teachers and students. Data in this research are documents in the form of lesson plans, and the result test conducted by student about the ability to understand the contents of fable text using the DRA method.The data collection technique used is the technique of direct observation. The results obtained in this study experienced improvement in every process. Based on the result of research in the first cycle the average value of student learning outcomes only reached 65.14 and is under the minimum value of the specified completeness criteria which is 72. In the second cycle average value of student learning outcomes reached 83, 90 which means it meets the minimum completeness criteria or is above the prescribed standard is 72 to 86% Percentage of completeness. Keywords: Ability, Reading Comprehension, Reading Directed Methods Activity